Occupational and environmental exposure to arsenic. Bibliographical update for research - Ramírez, Augusto (2013)
Arsenic is a metalloid present in ores containing copper and causes a severe occupational disease. The main occupational exposure occurs in copper metallurgy. It enters the human body by the respiratory, digestive and skin tracts. It is transformed into dimethylarsinic and methylarsonic acids that are excreted by urine, feces or skin. Its trivalent compounds are cumulative and might cause cancer in several organs. Arsenic binds with a covalent link to mercapto sulfur groups and it uncouples oxidative phosphorylation, suggesting a non-hydrolytic inhibitory action in mitochondria. Some fish and shellfish contain high amounts of organic arsenic. In subjects unexposed, in agreement to the diet inorganic arsenic is <5 ug/g creatinine. The biologic exposure index in workers is 35 ug/g creatinine measured at the end of a work week. The threshold level value in work environment is 0.01mg/m3. Arsine is the most toxic arsenical compound. Endemic regional hydroarsenicism is an environmental disease caused by water arsenic contents in some regions.